Pengaruh Rasio Capital Adequacy Ratio, Net Interest Margin, Non Performing Loan Terhadap Return on Asset Bank Konvensional Periode 2014 - 2022 - Ketut Adhi Wiyana Wirawan; A. A. Ketut Jayawarsa; I Komang Putra (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
This research serves to fill in the gaps in knowledge from previous studies that discuss different opinions about each ratio. The focus is on the phenomenon of gaps in the relationship between ROA and bank financial performance. The purpose is to evaluate the effect of Capital Adequacy Ratio, Net Interest Margin, and Non Performing Loan on ROA both separately and together at these banks during the period 2014-2022. This research method is a quantitative approach purposive sampling technique to select a sample consisting of five leading conventional banks in Indonesia. The results of the analysis using multiple linear regression and hypothesis testing, the effect of Capital Adequacy Ratio on ROA is not significant, Net Interest Margin has a significant positive effect on ROA, Non Performing Loan on ROA has a significant negative effect, Capital Adequacy Ratio, Net Interest Margin, Non Performing Loan as a whole has an effect on ROA.